Balinese Local Plants in Regulating Body Weight: A Review - Damayanti, Ida Ayu Manik; Megayanti, Sri Dewi; Wulansari, Nadya Treesna (Jurnal Pijar Mipa, 2025)
Obesity and overweight have become major global health concerns. In Indonesia, one in five school-aged children is overweight or obese, with increasing rates observed in Bali. Dietary imbalance, sedentary lifestyles, and metabolic dysregulation contribute to abnormal body weight gain. In light of the limitations of synthetic drugs, plant-derived bioactive compounds have attracted attention as safer and multi-target alternatives for regulating body weight. This review aims to synthesise current scientific evidence on the potential of Balinese local plants in regulating body weight, identify their bioactive compounds and underlying mechanisms, and highlight research gaps to guide future nutraceutical development. This systematic review, conducted in accordance with the PRISMA 2020 guidelines, examined literature published between 2020 and 2025 retrieved from PubMed, ScienceDirect, and Google Scholar. The keywords Balinese plants, body weight, obesity, anti-obesity, plant extract, and bioactive compounds, eight studies met the inclusion criteria. The identified Balinese local plants, including Clitoria ternatea, Zingiber cassumunar, Phyllanthus acidus, Murraya paniculata, Hibiscus rosa-sinensis, Elaeocarpus grandiflorus, Tagetes erecta, and Lagerstroemia speciosa, demonstrated significant potential in regulating body weight. Their mechanisms included AMPK activation, inhibition of pancreatic lipase, suppression of adipogenesis, induction of thermogenesis, and modulation of antioxidants. Balinese local plants exhibit multi-pathway potential in regulating body weight through metabolic and physiological modulation.